2005
DOI: 10.1111/j.1440-1746.2005.03944.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and isoforms of epimorphin in carbon tetrachloride‐induced acute liver injury in mice

Abstract: Epimorphin is involved in tissue repair following a single injection of carbon tetrachloride, in which distribution and the quantity of epimorphin expression are important, particularly in maintaining hepatocyte function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…The identification of the epimorphin binding cleft may facilitate development of inhibitors capable of blocking the binding of epimorphin to its cell surface receptors. Moreover, because epimorphin has been implicated in normal and pathological development of a number of organs in addition to the breast, including intestine (10,61), lung (62,63), pancreas (7), liver (64,65), cartilage (66), and hair (9, 67), our identification of a key epimorphin interaction domain may be applicable to investigations of these organs in both normal development and in neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the epimorphin binding cleft may facilitate development of inhibitors capable of blocking the binding of epimorphin to its cell surface receptors. Moreover, because epimorphin has been implicated in normal and pathological development of a number of organs in addition to the breast, including intestine (10,61), lung (62,63), pancreas (7), liver (64,65), cartilage (66), and hair (9, 67), our identification of a key epimorphin interaction domain may be applicable to investigations of these organs in both normal development and in neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our finding that epimorphin inhibition caused persistently increased macrophage and myofibroblast infiltration, cell proliferation and loss of E-cadherin expression on tubular epithelial cells strongly suggests that epimorphin functions basically in the repair of renal fibrosis possibly through mesenchymal-epithelial interaction. Considering what we know of tissue damage in other organs, [11][12][13][14][15] we assume that when a kidney is injured epimorphin functions as a repair protein and has a role similar to its role as a morphogen when a kidney develops.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] In addition, several investigators have reported changes in the distribution of epimorphin-positive cells in inflammatory diseases of the lung and liver. [11][12][13][14] Epimorphin not only regulates morphogenesis but also functions as a mesenchymal regulator of epithelial repair. 10,12,14,15 The importance of epithelial-mesenchymal transition in the development of renal fibrosis has been extensively analyzed and characterized.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Epimorphin is one of the ligands of the integrin aVb1 receptor located on the cellular membrane [31] and is expressed in hepatic stellate cells and myofibroblasts during liver injury in mice [32,33]. After binding to its receptor, epimorphin signals regulate normal bile duct formation by mediating mitosis orientation [34].…”
Section: Discussionmentioning
confidence: 99%